The relationship between ergonomic and employees performance at Supply Chain Management Department at level 53 Petroliam Nasional Berhad (PETRONAS) in Kuala Lumpur / Tengku Nurul Fatihah Tengku Razlan - Tengku Razlan, Tengku Nurul Fatihah (2015)
The purpose of this study is to identify the relationship between ergonomic with employees performance in Supply Chain Management, Petroliam Nasional Berhad (PETRONAS). There were three (3) research objectives to be study which is, to identify the factors of the ergonomics that will lead to the employee's performance, to evaluate the factor of ergonomics would contribute most to employee's performance and to determine the relationship between ergonomics in the workplace and the employee's performance. The scope of this research are limited as this research only focused on the employees' performance in the organization that have been selected which are located in Kuala Lumpur. The researchers will choose Supply Chain Management Department at level 53 in Petroliam Nasional Berhad (PETRONAS) in Kuala Lumpur as a place to conduct the research. Besides that research only takes consideration from the employee's perspectives to examine the aspects of the effectiveness of good ergonomics that have been provided by the organization that will lead to the employee performances. The number of population for this research is estimated for 107 respondents, however, only 87 respondents been choosing as a sample. This sample size is taken by referring to the sample size given population by Krejcie and Morgan (1970). The sample technique used are simple random sampling, whereas, this technique is least bias and offer the most generalizability on the selection of the respondents. The research finding can be concluding that there is positive relationship between ergonomic with employee performance in Supply Chain Management Department. This finding show that ergonomic is closely related with the employees' performances.